Cognitive Health and Differential Cortical Functioning in Dissociative Trance: An Explorative Study About Mediumship - Spindola-Rodrigues, Karleth Costa; Reis, Renandro de Carvalho; de Carvalho, Caio Macedo; de Siqueira, Socorro D’Paula Nayh Leite Loiola; Rocha Neto, Antonio Vitor da; Almeida, Kelson James (Frontiers in Psychology, 2022)
Aim: To evaluate the cognitive functioning of subjects practicing trance mediumship in Brazil. Method: The study was based on the measurement of cognitive functions of 19 spirits mediums through neuropsychological tests such as the Brief Cognitive Screening Battery (BCSB), the Verbal Fluency Test (FAS), the digit span test, the cube test, the five digit test (FDT) and an evaluation of mental health through scales such as the Beck Depression Inventory (BDI), the Self-Report Questionnaire (SRQ), and the Trauma History Questionnaire (THQ). The sample included the participation of spirit mediums divided into 2 groups. The more experienced group (MEG) with 11 subjects had more than 10 years of mediumistic practice, while the other less experienced group (LEG) with 8 subjects had 1 to 5 years of experience. The inclusion criteria were psychophonic mediums (who have the ability to communication when deceased beings communicate directly via speaking) with regular trance practices for at least one year. The data collected were analyzed using the SPSS statistical package. Results: Regarding performance on the BCSB and digit span test, all subjects reached scores at the median or higher in comparison to standardized scores of Brazilians. Scores of 90% on the cube test and 42% on the FAS were reached in comparison to median or higher values, versus the median of standardized scores among Brazilians. On the FDT, we found statistical significance (p = 0.038) in the choice stage, with higher performance of subjects whose initial age of trance recognition occurred before 21 years old. On the BDI scale, no participant met the criteria for major depression. The SRQ showed an incidence of common mental disorders in 21% of the sample, which was more prevalent in the LEG (p = 0.008). Conclusions: The cognitive functioning of subjects who practice trance mediumship in Brazil is associated with cognitive health. Executive dysfunction may be a tendency in LEG. However, an incidence of common mental disorders in the LEG was observed. Executive processing was higher in the subgroup with early practices of recognizing the phenomenon.